Obesity is associated with depression in Malaysian schoolchildren: A cross-sectional study - Nurumal, Mohd. Said; Zainal Abidin, Rohulizzat; Ibrahim, Wisam Nabeel; Md Isa, Muhammad Lokman; Che Hasan, Muhammad Kamil (Universitas Indonesia, 2020)
Background: Overweight and obesity, which may lead to depression, have become prevalent among children worldwide. Hence, this study aimed to measure obesity and depression among schoolchildren in Kuantan.